-2(3x+1)+18x=5x+16

Simple and best practice solution for -2(3x+1)+18x=5x+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3x+1)+18x=5x+16 equation:



-2(3x+1)+18x=5x+16
We move all terms to the left:
-2(3x+1)+18x-(5x+16)=0
We add all the numbers together, and all the variables
18x-2(3x+1)-(5x+16)=0
We multiply parentheses
18x-6x-(5x+16)-2=0
We get rid of parentheses
18x-6x-5x-16-2=0
We add all the numbers together, and all the variables
7x-18=0
We move all terms containing x to the left, all other terms to the right
7x=18
x=18/7
x=2+4/7

See similar equations:

| 3(-2x+11)+7x=20 | | 2.36=(1+x)^30 | | -9=-2r+-5 | | 2x+2x+9=-2+x+3x | | 4(6-2x)=1/2(4x+10) | | 2x+2x+9=-2+x* | | 4f=12/3 | | 86=6+8(n+4) | | 10y+35=5(2y+5) | | -3y^2-16y+75=0 | | 8x−9−4x=25 | | 9g-22=4g+18 | | 5x=20000 | | 8x‐2(x+9)=x+47 | | 5(4x-5)=-90 | | 10x+12=12x-10 | | -3(1+6n)+3n=87 | | `6x+8-2x=14+10x` | | 3x-16-5x=49 | | 3x-16x=40 | | (x+6)(x+5)=(x+2)(x-5) | | -5p-8=1+5p-9 | | x^2-((3/2)x)^2=4 | | 3x=131 | | x2=49/69 | | x2=49169 | | 13(17x-23)^2=156 | | 25+12x=6x+4 | | 21=-6x | | -3-4(7-4x)=81 | | 4+13(17x-23)^2=160 | | 5m-58=0 |

Equations solver categories